The Non-solventogenic Clostridium beijerinckii Br21 Produces 1,3-Propanediol From Glycerol With Butyrate as the Main By-Product - Mermejo, Beatriz da Cruz (2022)
Ever-increasing biofuel production has raised the supply of glycerol, an abundant waste from ethanolic fermentation and transesterification, for biodiesel production. Glycerol can be a starting material for sustainable production of 1,3-propanediol (1,3 PD), a valued polymer subunit. Here, we compare how Clostridium pasteurianum DSMZ 525, a well-known 1,3-PD-producer, and the non-solventogenic Clostridium beijerinckii Br21 perform during glycerol fermentation. Fermentative assays in 80-, 390-, or 1,100-mM glycerol revealed higher 1,3-PD productivity by DSMZ 525 compared to Br21. The highest 1,3-PD productivities by DSMZ 525 and Br21 were obtained in 390 mM glycerol: 3.01 and 1.70 mM h−1, respectively. Glycerol uptake by the microorganisms differed significantly: C. beijerinckii Br21 consumed 41.1, 22.3, and 16.3%, while C. pasteurianum consumed 93, 44.5, and 14% of the initial glycerol concentration in 80, 390, and 1,100 mM glycerol, respectively. In 1,100 mM glycerol, C. beijerinckii Br21 growth was delayed. Besides 1,3-PD, we detected butyrate and acetate during glycerol fermentation by both strains. However, at 80 mM glycerol, C. beijerinckii Br21 formed only butyrate as the by-product, which could help downstream processing of the 1,3-PD fermentation broth. Therefore, C. beijerinckii Br21, an unexplored biocatalyst so far, can be used to convert glycerol to 1,3-PD and can be applied in biofuel biorefineries.